The 2D: 4D Digit Ratio and Primary Sjogren's Syndrome: A Window Into Prenatal Hormonal Influences on Exocrine Autoimmunity reply - Gur, Mustafa; Akkoc, Ramazan Fazil; Oz, Burak; Karatas, Ahmet; Koca, Suleyman Serdar (Wiley, 2026)
[Abstract Not Available]
Keywords: [Keyword Not Available]